The influence of operational stiffness of structural components on the performance of deep excavations - Dong, Y; Burd, H; Houlsby, G (Taylor and Francis - Balkema, 2014)
The performance of deep excavations is affected by the stiffness of various structural components (e.g. retaining walls, horizontal struts, vertical piles). For reinforced concrete structures, the operational stiffness (i.e. the bending stiffness and axial stiffness under working conditions) may be different from the nominal stiffness due to imperfections in the concrete (e.g. cracks). In addition, the operational stiffness may change as the excavation proceeds. To investigate how the operational stiffness of the concrete structural components affects the predicted performance of excavations, finite element analyses were conducted on an example 3D basement excavation using a top-down construction method. Results indicate that the wall stiffness mainly influences the magnitude of the wall deflection and ground movements, whereas the stiffness of the horizontal beams and slabs influences both the magnitude and pattern of the deformation. This research can be used to select appropriate analysis procedures for design purposes, and for the prediction of the performance of completed deep excavations. © 2014 Taylor and Francis Group, London.